Secondary Pulmonary Alveolar Proteinosis - Lim, Jayleigh; Boyle, Niamh; McCarthy, Cormac (Seminars in Respiratory and Critical Care Medicine)
Pulmonary alveolar proteinosis (PAP) is a rare syndrome characterised by progressive accumulation of surfactant in pulmonary alveoli, resulting in hypoxemic respiratory insufficiency, and an increased risk of secondary infections and pulmonary fibrosis. Secondary PAP (sPAP) occurs because of an underlying disease that reduces the number and/or functions of alveolar macrophages, with haematological disorders being the commonest underlying cause. SPAP accounts for 4% of PAP cases, often occurs in the 4th decade of life, and has a slight male predominance. Patients with sPAP often present in the context of their underlying clinical condition. The prognosis of sPAP is considerably worse than aPAP, with an estimated median survival of less than 20 months. Given the nonspecific clinical presentation of PAP, its diagnosis requires appropriate serological, radiological, and bronchoscopic evaluation. The characteristic “crazy-paving” appearance described in aPAP might not always be present in sPAP. Ground glass opacifications in sPAP typically show a more diffuse pattern compared to a patchy geographic pattern seen in aPAP. The only proven therapy for sPAP is the treatment of the underlying disease, with whole lung lavage demonstrating efficacy in a small number of cases. In this review we discuss the presentation, prognosis and treatment of sPAP.